Development of Comic Book to Improve Reading Skills in Arabic Learning - Umami, Izzatul; Hidayah, Nurul (UAS PRESS, 2024)
The need to address the limited Arabic reading materials used by students at Madrasah Aliyah al-Bairuny is what prompted this research on comic book production. Creating and evaluating comic books as a means to improve reading skills was the main objective of this project. This study was developmental research using the five-stage ADDIE model (analysis, design, development, implementation, and evaluation). The study used observations, questionnaires, and tests to collect data. Educators with expertise in materials and media evaluated the feasibility of the product, and 25 tenth-grade students provided feedback. Experts deemed the comic highly valid for Arabic learning with an 87.5% rating, while students responded very positively, giving it a score of 82.16%. This comic has also been proven to improve Arabic reading skills based on the results of n-gain score test with an average value of 77.26% or in effective category. Based on the various assessment results that have been mentioned, it can be concluded that the comic is suitable and effective teaching material to be used as a 10th grade Arabic learning book.